A denitration catalyst, preparation method and application thereof
By using low-temperature denitrification catalysts prepared by natural zeolites and other oxide components, the efficiency and stability of existing catalysts under low temperature conditions are solved, and efficient and economical flue gas denitrification effect is achieved.
Patent Information
- Application Number
- CN202111194386.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-28
- Filing Date
- 2021-10-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-10-13
AI Technical Summary
The existing low-temperature denitrification catalysts have problems such as low ignition point, insufficient mechanical strength, susceptibility to sulfur water poisoning and high cost, which limits their application in the field of flue gas denitrification.
Natural zeolite is used as a support, combined with manganese ore powder, iron illuminate, pseudo-thin aluminite and nitric acid, and efficient low-temperature denitrification catalyst is prepared through kneading and extrusion molding.
It achieves efficient low-temperature denitrification performance, has a large specific surface area, high mechanical strength, is not prone to sulfur water poisoning and has low production cost, and is suitable for flue gas purification under low temperature conditions.
Smart Images

Figure CN113751019B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of chemical industry, especially the field of catalysts, and specifically to a denitration catalyst, a preparation method thereof and an application thereof. The denitration catalyst of the present application uses natural zeolite as a raw material and is a new, high-strength and high-efficiency denitration catalyst. Background Art
[0002] Flue gas denitrification refers to the process of reducing the generated nitrogen oxides to nitrogen, thereby removing nitrogen oxides from the flue gas. At present, the more mainstream denitrification processes are divided into selective catalytic reduction denitrification (abbreviated as: SCR) and selective non-catalytic reduction denitrification (abbreviated as: SNCR).
[0003] The core of SCR denitrification is the denitrification catalyst. According to the suitable reaction temperature of the catalyst, SCR denitrification catalyst can be divided into high temperature (>400℃), medium temperature (200-400℃) and low temperature (100-200℃) denitrification catalyst. When the oxygen content in the flue gas is excessive and the temperature is high (>350℃), ammonia oxidation will occur, which will not only consume ammonia but also generate new nitrogen oxides, causing a significant decrease in denitrification efficiency. Therefore, the development of low-temperature and high-efficiency SCR catalytic materials has become the focus of research at home and abroad.
[0004] According to the different catalyst carrier materials, low-temperature denitration catalysts can be divided into carbon materials, metal oxides and molecular sieves. Among them, the biggest defect of carbon material low-temperature denitration catalysts is that they have a low ignition point; in actual engineering, when the reaction temperature exceeds 175°C, the catalyst bed will be locally overheated and spontaneously combust. The advantages of metal oxide low-temperature denitration catalysts are excellent low-temperature activity and simple synthesis methods; but they have the defects of small specific surface area, low mechanical strength, easy sulfur water poisoning, and high cost, which restrict their industrial promotion and application. Molecular sieve low-temperature denitration catalysts have excellent denitration performance in the medium and high temperature range; compared with other denitration catalyst systems, the excellent thermal stability of molecular sieve low-temperature denitration catalysts is its biggest advantage; but the high cost of synthesizing molecular sieve catalysts limits their application.
[0005] At present, some patents in the prior art have disclosed corresponding denitration catalysts. For example, Chinese patent application CN111871450A discloses a CHA structure molecular sieve and a preparation method and application of its tail gas denitration catalyst, which uses N,N,N-trialkyl-(norbornane-2-yl) quaternary ammonium compound as an organic template to synthesize the CHA structure molecular sieve, wherein the molar ratio of silicon dioxide to aluminum oxide in the CHA structure molecular sieve is 6 to 80, the average crystal diameter is ≤500nm, and the total specific surface area is ≥400m 2 / g, total pore volume ≥0.20ml / g, micropore volume ≥0.10ml / g; the molecular sieve has a CHA topological structure, an X-ray crystal diffraction (-210) crystal plane half width (FWHM) range of 0.1-0.2°, and a grain diameter size in the crystal plane (-210) direction of 50-160nm; after the molecular sieve is treated with saturated water vapor at 600-850°C, the tetracoordinated aluminum accounts for ≥90% of the total aluminum, and the hexacoordinated aluminum accounts for ≤10% of the total aluminum.
[0006] Chinese patent application CN111589442A discloses the use of natural manganese ore in the preparation of a denitration catalyst, a denitration catalyst and a preparation method thereof. The denitration catalyst is prepared by a method comprising the following steps: (a) crushing the natural manganese ore and a carrier into natural manganese ore particles and carrier particles, respectively; (b) mixing the natural manganese ore particles, the carrier particles and an optional molding aid uniformly and pressing them into tablets to obtain a denitration catalyst precursor; (c) calcining the denitration catalyst precursor to obtain a denitration catalyst.
[0007] Chinese patent application CN110756217A discloses a denitration catalyst, a preparation method and an application thereof, which comprises the following components based on the total weight of the catalyst: a) 10-50wt%, preferably 20-40wt% of Fe-type mordenite; b) 30-60wt%, preferably 40-60wt% of anatase TiO2; c) 5-20wt%, preferably 5-10wt% of aluminum oxide; d) 1-10wt%, preferably 2.5-8wt% of an oxide of at least one selected from the group consisting of cerium, manganese, vanadium, cobalt and copper; e) 1-10wt%, preferably 1-7wt% of an oxide of at least one selected from the group consisting of niobium, tungsten, molybdenum and tin.
[0008] For the technology in this field, it is particularly important to develop a molecular sieve denitrification catalyst with good denitrification performance, resistance to sulfur and water, and low cost. Summary of the invention
[0009] The purpose of the invention of this application is to provide a denitration catalyst, a preparation method and application thereof in view of the above-mentioned problems.
[0010] One of the invention purposes of the present application is to provide a denitration catalyst. With natural zeolite as the carrier, the catalyst has the characteristics of large specific surface area, high mechanical strength, not easy to be poisoned by sulfur water, low production cost, applicable to low temperature conditions, and good denitration performance. The present application has good low-temperature denitration efficiency, has important practical significance for improving the level of flue gas purification, and is a breakthrough invention in the field of flue gas denitration.
[0011] The second purpose of the invention of this application is to provide a method for preparing the above-mentioned denitration catalyst, which has readily available raw materials, a simple preparation process, low production cost, can meet the needs of industrialized and large-scale production applications, and has extremely high application value.
[0012] The third purpose of the invention of this application is to claim the application of the above-mentioned denitration catalyst in the field of denitration. Experimental data show that the catalyst of this application can be used at a space velocity of 10000h -1 When the nitrogen oxides are reduced, it still has a very high denitrification rate, which is of great significance to the quality of nitrogen oxides.
[0013] In order to achieve the above purpose, this application adopts the following technical solutions:
[0014] A denitration catalyst is prepared from raw materials including the following components: zeolite, manganese ore powder, ferrotitanium powder, pseudo-boehmite, and nitric acid;
[0015] The sum of zeolite, manganese ore powder and ferrotitanium powder is recorded as a first intermediate, wherein the mass fraction of manganese is 12-18 wt % and the mass fraction of titanium is 2-5 wt %;
[0016] The mass of the pseudo-boehmite is 4-8wt% of the mass of the first intermediate material.
[0017] The mass of the sesbania powder is 0.8-2.0wt% of the mass of the first intermediate material;
[0018] The mass of the nitric acid is 8-13 wt % of the mass of the first intermediate material, calculated as HNO 3 in the nitric acid.
[0019] The zeolite is natural zeolite.
[0020] The mass fraction of manganese in the manganese ore powder is 50-69%, and the mass fraction of titanium in the ferrotitanium powder is 20-60%.
[0021] The purity of the pseudo-boehmite is 70-80%.
[0022] Preferably, the mass fraction of manganese in the manganese ore powder is 60-69%, and the mass fraction of titanium in the ferrotitanium powder is 30%.
[0023] The purity of the pseudo-boehmite is 80%.
[0024] The concentration of the nitric acid is 30% to 70%. Preferably, the concentration of the nitric acid is 68%.
[0025] The preparation method of the above-mentioned denitration catalyst comprises the following steps:
[0026] (1) sieving natural zeolite, manganese ore powder and ferrotitanium powder respectively for later use;
[0027] Weigh natural zeolite, manganese ore powder and ferrotitanium powder according to a ratio, and mix them to obtain a first intermediate; in the first intermediate, the mass fraction of manganese is 12 to 18 wt%, and the mass fraction of titanium is 2 to 5 wt%;
[0028] (2) Weighing pseudo-boehmite and sesbania powder according to the ratio, adding the weighed pseudo-boehmite and sesbania powder to the first intermediate, and mixing them evenly using a kneader to obtain a second intermediate;
[0029] The masses of the pseudo-boehmite and sesbania powder are 4-8wt% and 0.8-2.0wt% of the mass of the first intermediate respectively;
[0030] (3) weighing nitric acid according to the ratio, and adding the weighed nitric acid to the second intermediate to obtain a third intermediate;
[0031] The mass of the nitric acid is 8 to 13 wt % of the mass of the first intermediate material, calculated as HNO3 in the nitric acid;
[0032] (4) kneading the third intermediate product, and sending the kneaded material to an extruder, and extruding it at 10 to 15 MPa to obtain an extruded strip;
[0033] (5) Drying the prepared extruded strip at 90-125° C. for 5-8 hours to obtain a dried strip; and calcining the dried strip at 300-650° C. for 2-3 hours to obtain a denitration catalyst.
[0034] In the step 1, the natural zeolite, manganese ore powder and ferrotitanium powder are respectively passed through a 100-400 mesh sieve for standby use. Preferably, the natural zeolite, manganese ore powder and ferrotitanium powder are respectively passed through a 200 mesh sieve for standby use.
[0035] In the step 4, the third intermediate product is kneaded for a time of 30 min to 300 min.
[0036] In the step 5, the calcination temperature is 400-600°C.
[0037] The application of the aforementioned denitration catalyst in flue gas denitration.
[0038] The prepared catalyst is applied to flue gas denitrification, and the flue gas temperature is 100-350°C.
[0039] The prepared catalyst was applied to flue gas denitrification, with a flue gas temperature of 180-220°C and a space velocity of 1000 h -1 -15000h -1 .
[0040] In view of the above problems, the present application provides a denitration catalyst, a preparation method and application thereof. The present application uses natural zeolite as a carrier, which has the advantage of low cost compared to synthetic molecular sieves. Manganese ore powder is the source of manganese, and manganese is the active site of the catalyst, which is conducive to the NH3-SCR reaction.
[0041] In the present application, the addition of nitric acid will not only enhance the mechanical strength of the catalyst prepared by natural zeolite after molding, but also affect the distribution of the total acid content and acid strength on the catalyst surface, thereby affecting the reaction effect of NH3-SCR. Pseudo-boehmite affects the strength of the molded catalyst to a certain extent, and also affects the pore structure of the catalyst, thereby affecting the adsorption performance of the catalyst and the catalytic efficiency. The addition of sesbania powder reduces the friction between the material particles and between the powder and the mold equipment during the catalyst extrusion molding process, protects the mold, and allows the pressure generated by the extrusion to be evenly transmitted to the powder particles filled therein, thereby obtaining a strip catalyst with uniform mechanical strength. In the present application, a kneading machine is used for kneading, so that each powder material is fully in contact with the nitric acid solution and reacts and mixes.
[0042] The test results show that the denitration catalyst of the present invention is a highly efficient low-temperature denitration catalyst with excellent catalytic performance. Compared with the existing denitration catalysts, it has achieved significant progress under the same low-temperature flue gas conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The present invention will now be described by way of example with reference to the accompanying drawings, in which:
[0044] Figure 1 This is a diagram of the material properties after complete kneading in Example 1.
[0045] Figure 2 This is the extrusion effect diagram in Example 1.
[0046] Figure 3 This is a picture of the calcined product of the material in Example 1.
[0047] Figure 4 The N2 selectivity of the products obtained at different calcination temperatures at different denitrification temperatures.
[0048] Figure 5 It is the denitrification rate of the product at different space velocities and different denitrification temperatures.
[0049] Figure 6 It is the N2 selectivity of the product at different space velocities and different denitrification temperatures. DETAILED DESCRIPTION
[0050] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.
[0051] Any feature disclosed in this specification, unless otherwise stated, can be replaced by other equivalent or alternative features with similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.
[0052] (I) Sample preparation
[0053] In this embodiment, the experimental materials used are shown in Table 1 below.
[0054] Table 1 Experimental materials
[0055] raw materials Specifications and dimensions Remark Natural zeolite (Natural Mineral Collection) Clinoptilolite Powder Manganese powder 200 mesh, containing Mn 69% Powder Ferrotitanium powder Ti30%, 200 mesh Powder Pseudoboehmite 80% Powder Sesbania powder Food Grade Powder Concentrated nitric acid 68% liquid Industrial soft water liquid
[0056] In this embodiment, the experimental equipment is shown in Table 2 below.
[0057] Table 2 Experimental equipment
[0058] Serial number Device Name Specifications and dimensions quantity Remark 1 Kneading machine HQ50L 1 set 2 Extruder JPS50 1 set Working pressure 12Mpa 3 High temperature oven Effective volume 200L 1 set 4 Automatic particle strength tester KQ-3 1 set
[0059] Example 1
[0060] (1) Natural zeolite, manganese ore powder and ferrotitanium powder were sieved through 200 meshes respectively. Then, 7.3 kg of natural zeolite, 2.1 kg of manganese ore powder and 1.1 kg of ferrotitanium powder after sieve were weighed and mixed to obtain a first intermediate. In the first intermediate, the mass fraction of manganese was 13.8 wt % and the mass fraction of titanium was 3.1 wt %.
[0061] (2) Weigh 0.7 kg of pseudo-boehmite and 0.14 kg of sesbania powder respectively, add the weighed pseudo-boehmite and sesbania powder to the first intermediate, and mix them evenly using a kneader to obtain a second intermediate.
[0062] (3) Take 1.65 kg of concentrated nitric acid with a mass fraction of 68%, dilute it with 1.65 kg of water, and obtain a second mixed solution. Slowly add the second mixed solution to the second intermediate to obtain a third intermediate. The mass of the nitric acid is 10.7 wt % of the mass of the first intermediate, based on the HNO3 in the nitric acid.
[0063] (4) The third intermediate product is sent to the kneader and kneaded for 40 minutes (the material properties after kneading are as shown in the figure below) Figure 1 As shown), transferred to a strip extruder, extruded under a pressure of 12Mpa to obtain an extruded strip (the extrusion effect diagram is shown in Figure 2 shown).
[0064] (5) The extruded strip obtained in step (4) was placed in an oven and dried at 105°C for 5 hours. Then, it was calcined at 400°C, 500°C or 600°C for 3 hours to obtain a strip-shaped catalyst with a diameter of about 3 mm (the properties of the material after calcination are shown in the figure). Figure 3 shown).
[0065] Example 2
[0066] In this embodiment, the preparation method of the denitration catalyst is as follows.
[0067] (1) Pass natural zeolite, manganese ore powder and ferrotitanium powder through a 200-mesh sieve respectively. Then, weigh the sieved natural zeolite, manganese ore powder and ferrotitanium powder according to the proportion, and mix them to obtain a first intermediate. In the first intermediate, the mass fraction of manganese is 15-16wt%, and the mass fraction of titanium is 3-4wt%.
[0068] (2) Pseudo-boehmite and sesbania powder are weighed according to the ratio, added to the first intermediate, and mixed evenly by a kneader to obtain a second intermediate, wherein the weight of the pseudo-boehmite and sesbania powder is 5-6wt% and 1.4-1.5wt% of the weight of the first intermediate, respectively.
[0069] (3) diluting concentrated nitric acid with a mass fraction of 68% with industrial water to obtain a second mixed solution. Slowly adding the second mixed solution to the second intermediate to obtain a third intermediate. The mass of the nitric acid is 10-11 wt % of the mass of the first intermediate based on the HNO3 in the nitric acid.
[0070] (4) The third intermediate product was fed into a kneader and kneaded for 45 minutes, and then transferred to a strip extruder and extruded at a pressure of 12 MPa to obtain an extruded strip.
[0071] (5) The extruded strip obtained in step (4) was placed in an oven and dried at 105° C. for 7 h. Then, it was calcined at 400° C. for 3 h to obtain a low-temperature natural zeolite denitrification catalyst.
[0072] Example 3
[0073] In this embodiment, the preparation method of the denitration catalyst is as follows.
[0074] (1) Pass natural zeolite, manganese ore powder and ferrotitanium powder through a 200-mesh sieve respectively. Then, weigh the sieved natural zeolite, manganese ore powder and ferrotitanium powder according to the proportion, and mix them to obtain a first intermediate. In the first intermediate, the mass fraction of manganese is 15-16wt%, and the mass fraction of titanium is 3-4wt%.
[0075] (2) Pseudo-boehmite and sesbania powder are weighed according to the ratio, added to the first intermediate, and mixed evenly by a kneader to obtain a second intermediate, wherein the weight of the pseudo-boehmite and sesbania powder is 5-6wt% and 1.4-1.5wt% of the weight of the first intermediate, respectively.
[0076] (3) diluting concentrated nitric acid with a mass fraction of 68% with industrial water to obtain a second mixed solution. Slowly adding the second mixed solution to the second intermediate to obtain a third intermediate. The mass of the nitric acid is 10-11 wt % of the mass of the first intermediate based on the HNO3 in the nitric acid.
[0077] (4) The third intermediate product was fed into a kneader and kneaded for 45 minutes, and then transferred to a strip extruder and extruded at a pressure of 12 MPa to obtain an extruded strip.
[0078] (5) The extruded strip obtained in step (4) was placed in an oven and dried at 105° C. for 7 h. Then, it was calcined at 500° C. for 2 h to obtain a low-temperature natural zeolite denitrification catalyst.
[0079] Example 4
[0080] In this embodiment, the preparation method of the denitration catalyst is as follows.
[0081] (1) Pass natural zeolite, manganese ore powder and ferrotitanium powder through a 200-mesh sieve respectively. Then, weigh the sieved natural zeolite, manganese ore powder and ferrotitanium powder according to the proportion, and mix them to obtain a first intermediate. In the first intermediate, the mass fraction of manganese is 12-14wt%, and the mass fraction of titanium is 2-3wt%.
[0082] (2) Pseudo-boehmite and sesbania powder are weighed according to the ratio, added to the first intermediate, and mixed evenly by a kneader to obtain a second intermediate, wherein the weight of the pseudo-boehmite and sesbania powder is 4-5wt% and 0.8-1.2wt% of the weight of the first intermediate, respectively.
[0083] (3) diluting concentrated nitric acid with a mass fraction of 68% with industrial water to obtain a second mixed solution. Slowly adding the second mixed solution to the second intermediate to obtain a third intermediate. The mass of the nitric acid is 8 to 10 wt % of the mass of the first intermediate, based on the HNO3 in the nitric acid.
[0084] (4) The third intermediate product was fed into a kneader and kneaded for 40 minutes, and then transferred to a strip extruder and extruded at a pressure of 12 MPa to obtain an extruded strip.
[0085] (5) The extruded strip obtained in step (4) was placed in an oven and dried at 105° C. for 6 h. Then, it was calcined at 450° C. for 2.5 h to obtain a low-temperature natural zeolite denitrification catalyst.
[0086] Example 5
[0087] In this embodiment, the preparation method of the denitration catalyst is as follows.
[0088] (1) Pass natural zeolite, manganese ore powder and ferrotitanium powder through a 100-mesh sieve respectively. Then, weigh the sieved natural zeolite, manganese ore powder and ferrotitanium powder according to the proportion, and mix them to obtain a first intermediate. In the first intermediate, the mass fraction of manganese is 16-17wt%, and the mass fraction of titanium is 2-3wt%.
[0089] (2) Pseudo-boehmite and sesbania powder are weighed according to the proportion, and the weighed pseudo-boehmite and sesbania powder are added to the first intermediate, and mixed evenly by a kneader to obtain a second intermediate. The weight of the pseudo-boehmite and sesbania powder is 5-6wt% and 1.2-1.4wt% of the weight of the first intermediate, respectively.
[0090] (3) diluting concentrated nitric acid with a mass fraction of 68% with industrial water to obtain a second mixed solution. Slowly adding the second mixed solution to the second intermediate to obtain a third intermediate. The mass of the nitric acid is 11-12 wt % of the mass of the first intermediate based on the HNO3 in the nitric acid.
[0091] (4) The third intermediate product was fed into a kneader and kneaded for 30 min, and then transferred to a strip extruder and extruded at a pressure of 12 MPa to obtain an extruded strip.
[0092] (5) The extruded strip obtained in step (4) was placed in an oven and dried at 105° C. for 8 h. Then, it was calcined at 400° C. for 3 h to obtain a low-temperature natural zeolite denitrification catalyst.
[0093] Example 6
[0094] In this embodiment, the preparation method of the denitration catalyst is as follows.
[0095] (1) Natural zeolite, manganese ore powder and ferrotitanium powder are sieved through a 300-mesh sieve respectively. Then, the sieved natural zeolite, manganese ore powder and ferrotitanium powder are weighed and mixed according to the proportion to obtain a first intermediate. In the first intermediate, the mass fraction of manganese is 17-18wt%, and the mass fraction of titanium is 4-5wt%.
[0096] (2) Pseudo-boehmite and sesbania powder are weighed according to the proportion, and the weighed pseudo-boehmite and sesbania powder are added to the first intermediate, and mixed evenly by a kneader to obtain a second intermediate. The mass of the pseudo-boehmite and sesbania powder is 6-8wt% and 1.6-1.8wt% of the mass of the first intermediate, respectively.
[0097] (3) diluting concentrated nitric acid with a mass fraction of 68% with industrial water to obtain a second mixed solution. Slowly adding the second mixed solution to the second intermediate to obtain a third intermediate. The mass of the nitric acid is 12-13 wt % of the mass of the first intermediate based on the HNO3 in the nitric acid.
[0098] (4) The third intermediate product was fed into a kneader and kneaded for 30 min, and then transferred to a strip extruder and extruded at a pressure of 12 MPa to obtain an extruded strip.
[0099] (5) The extruded strip obtained in step (4) was placed in an oven and dried at 105° C. for 8 h. Then, it was calcined at 500° C. for 2.5 h to obtain a low-temperature natural zeolite denitrification catalyst.
[0100] (II) Performance measurement
[0101] 1. The denitration catalyst prepared in Example 1 was tested, and the test conditions are shown in Table 3. Table 4 shows the denitration efficiency and N2 selectivity of the denitration catalysts prepared at different calcination temperatures at different denitration temperatures.
[0102] Table 3 Denitrification test conditions
[0103] NO(ppm) <![CDATA[NH3(ppm)]]> <![CDATA[O2(%)]]> Total flow rate (mL / L) <![CDATA[Air speed (h -1 )]]> 400 400 5 200 2000
[0104] Table 4 Denitrification efficiency (unit: %) and N2 selectivity (unit: %) of products with different calcination temperatures at different denitrification temperatures
[0105]
[0106]
[0107] It can be seen from Table 4 that the denitrification rate, i.e., NO conversion rate, of the products calcined at different temperatures is 100% at 150°C, 175°C, and 200°C. Considering the comprehensive energy consumption, the optimal preparation condition is tentatively determined to be 400°C.
[0108] The NO conversion rate, i.e. the denitration rate of the catalyst, is calculated as follows:
[0109]
[0110] Where:
[0111] λ——NO conversion rate, %;
[0112] c(NO) in ——NO concentration at the reactor inlet, in ppm;
[0113] c(NO) out ——Concentration of NO at the reactor outlet, in ppm.
[0114] In GB / T 38219-2019 Technical Specification for Flue Gas Denitrification Catalyst Detection, N2 selectivity refers to the conversion of NO x , and the proportion of N2 produced rather than N2O in the total number of NH3 molecules.
[0115] The catalyst N2 selectivity S is calculated as follows:
[0116]
[0117] Where:
[0118] S——catalyst selectivity, %;
[0119] ——N2O concentration at the reactor outlet (standard state, dry basis), in microliters per liter (μL / L);
[0120] —— Reactor inlet NO x Concentration (standard state, dry basis), unit is microliter per liter (μL / L);
[0121] ——Reactor outlet NO x Concentration (standard state, dry basis), unit is microliter per liter (μL / L);
[0122] ——NH3 concentration at the reactor inlet (standard state, dry basis), in microliters per liter (μL / L);
[0123] ——NH3 concentration at the reactor outlet (standard state, dry basis), in microliters per liter (μL / L).
[0124] Figure 4 The N2 selectivity of products obtained at different calcination temperatures at different denitrification temperatures is given. Figure 4 It can be seen that the N2 conversion rate of the products calcined at 400℃ and 500℃ reached the highest value of 92.7% and 92.6% at 150℃, respectively, with little difference. As the denitration temperature increases, the N2 conversion rate of the product decreases. At 600℃, it is 88.9% and 90%, respectively.
[0125] 2. Example 1 The denitration and N2 selectivity performance of the denitration catalyst obtained by calcining at 400°C were measured. Table 6 shows the denitration efficiency and N2 selectivity of the product at 400°C at different space velocities. The test conditions are shown in Table 5. In Table 5, the total flow rate corresponds to the space velocity; for example, when the total flow rate is 200mL / L, the space velocity is 2000h / L. -1 ; When the total flow rate is 500mL / L, the space velocity is 5000h -1 ; When the total flow rate is 1000mL / L, the space velocity is 10000h -1 .
[0126] Table 5 Denitrification test conditions
[0127] NO(ppm) <![CDATA[NH3(ppm)]]> <![CDATA[O2(%)]]> Total flow rate (mL / L) <![CDATA[Air speed (h -1 )]]> 400 400 5 200 / 500 / 1000 2000 / 5000 / 10000
[0128] Table 6 Denitrification efficiency and N2 selectivity of 400℃ products at different space velocities
[0129]
[0130] Figure 5 , Figure 6 The denitrification efficiency and N2 selectivity of the products at different space velocities and different denitrification temperatures are given respectively. Figure 5 It can be seen that the airspeed is 2000h -1 The denitrification efficiency of the product reaches 100% at 150℃, 175℃ and 200℃. When the air velocity is increased to 5000h -1 and 10000h -1 Under the denitration condition of 150℃, the denitration efficiency decreased significantly, falling to 95.1% and 52.9% respectively. As the temperature increases, the effect of the space velocity on the denitration efficiency decreases. The space velocity is 5000h -1 When the denitration efficiency is maintained at 100% under the conditions of 175℃ and 200℃, the air velocity increases to 10000h -1 When the temperature is 175℃, the denitration efficiency is reduced from 100% to 72.2%, and the denitration efficiency is maintained at 100% under the condition of 200℃. Figure 6 It can also be seen that the N2 selectivity of the product decreases with the increase of denitration temperature and increases with the increase of space velocity. The overall N2 selectivity is >82.8%.
[0131] From the above changes, it can be concluded that the natural zeolite denitrification catalyst prepared under this condition has a gas velocity of 2000h -1 The denitration temperature range is between 150℃ and 200℃, showing good denitration performance. -1 , denitration temperature between 175℃~200℃, showing good denitration performance. -1, denitrification temperature ≥200℃, showing good denitrification performance.
[0132] 3. The denitration catalyst obtained by calcining at 400°C in Example 1 was tested for its resistance to sulfur water. The test conditions are shown in Table 7. Table 8 shows the product at 400°C and at 5000h -1 Anti-sulfur water performance.
[0133] Table 7 Anti-hydrophobic performance test conditions
[0134] NO(ppm) <![CDATA[NH3(ppm)]]> <![CDATA[O2(%)]]> water(%) <![CDATA[Sulfur dioxide (mg / m 3 )]]> Total flow rate (mL / L) <![CDATA[Air speed (h -1 )]]> 400 400 5 10 35 500 5000
[0135] Table 8 Anti-hydrophobic performance test conditions
[0136]
[0137] 4. Table 9 shows the strength and denitration performance test results of products with different nitric acid contents. Table 9 shows that the denitration catalyst prepared in this application meets the requirements of GB / T10504-2017 standard.
[0138] Table 9 Strength and denitrification performance of products with different nitric acid contents
[0139] Nitric acid mass fraction / % Average crushing strength / N 6 Unformed detection 8 33.2 10 35.3 12.1 60.2
[0140] Table 10 Product performance under the condition of nitric acid content of 12.1wt%
[0141]
[0142] The present invention is not limited to the above-mentioned specific embodiments, but extends to any new features or any new combination disclosed in this specification, as well as any new method or process steps or any new combination disclosed.
Claims
1. A method for preparing a denitration catalyst, characterized in that: The invention is prepared from raw materials including the following components: natural zeolite, manganese ore powder, ferrotitanium powder, pseudo-boehmite, sesbania powder and nitric acid; The steps include: (1) Sieve the natural zeolite, manganese ore powder and ferrotitanium powder respectively and set aside; Weigh natural zeolite, manganese ore powder and ferrotitanium powder according to the proportion, mix them and obtain a first intermediate; the sum of the natural zeolite, manganese ore powder and ferrotitanium powder is recorded as the first intermediate, in which the mass fraction of manganese is 12-18wt%, and the mass fraction of titanium is 2-5wt%; (2) Weighing pseudo-boehmite and sesbania powder respectively according to the ratio, adding the weighed pseudo-boehmite and sesbania powder to the first intermediate, and mixing them evenly using a kneader to obtain a second intermediate; The masses of the pseudo-boehmite and sesbania powder are 4-8wt% and 0.8-2.0wt% of the first intermediate material respectively; (3) Weighing nitric acid according to the ratio, and adding the weighed nitric acid to the second intermediate to obtain a third intermediate; The mass of the nitric acid is 8-13wt% of the mass of the first intermediate material, calculated as HNO3 in the nitric acid; (4) kneading the third intermediate product, and sending the kneaded material to an extruder for extrusion at 10-15 MPa to obtain an extruded strip; (5) drying the prepared extruded strip at 90-125° C. for 5-8 hours to obtain a dried strip; and calcining the dried strip at 300-650° C. for 2-3 hours to obtain a denitration catalyst; The mass fraction of manganese in the manganese ore powder is 50-69%, and the mass fraction of titanium in the ferrotitanium powder is 20-60%; In the step 5, the calcination temperature is 400-600°C.
2. The preparation method according to claim 1, characterized in that: The mass fraction of manganese in the manganese ore powder is 60-69%, and the mass fraction of titanium in the ferrotitanium powder is 30%.
3. The preparation method according to claim 1, characterized in that: The purity of the pseudo-boehmite is 70-80%.
4. The preparation method according to claim 3, characterized in that: The purity of the pseudo-boehmite is 80%.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The concentration of the nitric acid is 30% to 70%.
6. The preparation method according to claim 5, characterized in that: The concentration of the nitric acid is 68%.
7. The preparation method according to claim 1, characterized in that: In the step 1, the natural zeolite, manganese ore powder and ferrotitanium powder are respectively sieved through a 100-400 mesh sieve for later use.
8. The product prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The invention is prepared from raw materials including the following components: natural zeolite, manganese ore powder, ferrotitanium powder, pseudo-boehmite and nitric acid.
9. Use of the denitration catalyst according to claim 8 in flue gas denitration.
10. The use according to claim 9, characterized in that: The prepared catalyst is applied to flue gas denitrification, and the flue gas temperature is 100-350°C.
11. The use according to claim 9 or 10, characterized in that: The prepared catalyst was applied to flue gas denitrification with a flue gas temperature of 180-220 °C and a space velocity of 1000 h -1 -15000 h -1 .
Citation Information
Patent Citations
Denitration catalyst and preparation method and application thereof
CN110756217A
CHA structure molecular sieve as well as preparation method and application of tail gas denitration catalyst of the CHA structure molecular sieve
CN111871450A
Honeycombed catalyst for low-temperature denitration and preparation method
CN105195171A
Medium and low temperature SCR (selective catalytic reduction) catalyst with wide use temperature and preparation method thereof
CN105903478A
Application of natural manganese ore in preparation of denitration catalyst, denitration catalyst and preparation method of denitration catalyst
CN111589442A